Analysis of Disaster Safe School Level in West Coast of Pandeglang Regency, Indonesia - Widana, I Dewa Ketut Kerta; Asmaniati, Fetty; Djati, Sundring Pantja; Ingkadijaya, Rahmat (Technium Social Sciences Journal, 2021)
Natural disasters are detrimental to many sectors, including the education sector. Schools located in disaster-prone areas are vulnerable to building damages, causing fatalities and psychological problems for students. Pandeglang Regency, especially on its west coast, is a tsunami-prone area and is home to hundreds of elementary to high schools in the area. The purpose of this study is to analyze the implementation of disaster safe schools in three schools with high vulnerability to tsunami: MTs Masyariqul Anwar, SDN Tamanjaya 2, and SD Mekarjaya 3. This research used disaster school survey form issued by National Disaster Management Agency (BNPB) which regulated in Head of BNPB Regulation No. 4 of 2012 on Implementation Guidelines of Disaster Safe Schools. The research findings are MTs Masyariqul Anwar and SDN Tamanjaya 2 have a sufficient safe school level but needs improvement in integrating disaster risk reduction curriculum and strengthening SOPs for safe schools, while SDN Mekarjaya 3 has a poor safe school level which lacking in both structural and non-structural frameworks. This study suggests that efforts to implement disaster safe schools are hampered due to the absence of a curriculum based on disaster risk reduction and poor infrastructure conditions. Thus, cooperation between local government, private sector, civic organizations, and the community is strongly needed in realizing a disaster safe school in Pandeglang Regency.